2009
DOI: 10.1161/strokeaha.108.538405
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen-Only Contraceptives and the Risk of Stroke

Abstract: Background and Purpose-The association between combined oral contraceptives (OC) use and increased risk of stroke has been reported. While progestogen-only contraceptives (POC) are commonly used worldwide, their impact on cardiovascular disease remains unclear. Methods-A meta-analysis based on EMBASE and MEDLINE referenced literature corresponding to OCs marketed since 1960 was carried out. Eligible articles assessing the risk of stroke in relation to OC or POC were reviewed, and relevant studies were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 38 publications
2
36
0
3
Order By: Relevance
“…217 Lastly, a systematic review of progestogen-only OCs revealed no significant increased risk of stroke with this form of contraceptive. 218 Two additional large cohort studies have been published since these meta-analyses. The first is the Women's Lifestyle and Health Cohort Study.…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…217 Lastly, a systematic review of progestogen-only OCs revealed no significant increased risk of stroke with this form of contraceptive. 218 Two additional large cohort studies have been published since these meta-analyses. The first is the Women's Lifestyle and Health Cohort Study.…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…[19][20][21][22][23] Although arterial events are less common than venous thromboembolism in women of reproductive age, the sequelae of stroke and myocardial infarction may be more devastating than those of venous thromboembolism. A large Danish cohort study found that women aged 45-49 years had 20 times the risk of stroke and 100 times the risk of myocardial infarction as women aged [15][16][17][18][19]. In this cohort, estrogen-containing contraceptive use increased the overall risk of stroke by as much as 2.2 times and of myocardial infarction by as much as 2.3 times.…”
Section: Cardiovascular Eventsmentioning
confidence: 81%
“…15 Two recent meta-analyses showed no association between progestin-only methods and arterial events. 16,17 Use of estrogen-containing contraceptives increases the risk of venous and arterial thromboembolic events. Other risk factors include, but are not limited to, age, obesity, smoking, diabetes, hypertension, migraine headaches (with or without aura) and thrombogenic mutations.…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…Oral contraceptives have been reported to be a risk factor for stroke, with an increased risk by about 4 times for pills with a high estrogen content, twice for pills with low estrogen content, and no increased risk for pills with progestagen alone. 31 However, stroke risks with oral contraceptives also appear to be modified by the presence of migraine and prothrombotic genetic variants. 8 Data on oral contraceptive use were only available for about one third of the female patients in sifap, in whom a prevalence of 30.5% was found.…”
Section: Discussionmentioning
confidence: 99%